Persepsi Guru terhadap Proses Pembelajaran pada Era Pascapandemi - Nuryansyah Adijaya; Zain, M. Yanuardi (STKIP PGRI Bandar Lampung, 2024)
Post-pandemic era is a situation after pendemic Covid-19 that hits almost every part of the world. The situation forces many people to create a new strategy in their life, including in learning-teaching process. In this era, the use of information technology through gadgets is considered the best way to conduct the learning process, provide teaching materials, and more. Moreover, the use of gadgets is seen as a tool that can connect both teachers and students to the global world, making information easily accessible to enrich the teaching materials used. This indicates that information technology through gadgets plays a crucial role in the learning process. However, the question arises whether the paradigm regarding the importance of gadgets in learning during the pandemic era also persists in the post-pandemic era. Therefore, this research aims to understand teachers' perceptions of the learning process in the post-pandemic era to explore learning processes in this period. Qualitative descriptive research, using interview and observation methods, was employed to gather data on post-pandemic era learning from two teachers in Jakarta Timur, Depok and Bogor. The results of this research show that teachers still believe that bringing gadgets into the learning process at school can have a negative impact on students. This is because gadgets may disrupt students' concentration by engaging in activities such as playing games or using social media. As a result, the teachers prohibit students from bringing gadgets into the classroom. These findings indicate that gadgets are still considered negative when brought into the learning process, proving that the learning paradigm during the pandemic era, which relied on information technology in the form of gadgets, is not applicable to some teachers, as evidenced by the prohibition of students bringing gadgets into the classroom.